2019
DOI: 10.1007/s10237-019-01254-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient materially nonlinear $$\mu$$FE solver for simulations of trabecular bone failure

Abstract: An efficient solver for large-scale linear FE simulations was extended for nonlinear material behavior. The material model included damage-based tissue degradation and fracture. The new framework was applied to 20 trabecular biopsies with a mesh resolution of 36 μm. Suitable material parameters were identified based on two biopsies by comparison with axial tension and compression experiments. The good parallel performance and low memory footprint of the solver were preserved. Excellent correlation of the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…[42]; DPY, Drucker-Prager yield; DLY, Drucker-Lode yield; PSD, principle strain damage [29]; LFD, Lee-Fenves plastic damage [22]; 1DY, one-dimensional yield; BM, Burger model; VMY, von Mises yield; VM+C+D, von Mises yield+cap+ element deletion; CIY, cast iron yield; BD, Brittle damage [17]; DPY(Q)+D, DPY(Q)+densification [19]; CZM, cohesive zone model; PFM, phase-field model; DPD+D, DP+Q damage onset+element deletion; GMM, generalized Maxwell model found: first, direct homogenization of the apparent level by using bone density (power laws [16,45]) and, in some cases, the orientation of the trabecular network (fabric [31,32] Damage and Fracture Interestingly, models including fracture mechanics became increasingly popular in the last years. Either rather simple "element deletion" models [46,51] or more sophisticated fracture energy-based models [26,45] have been published. Such approaches are more and more used in engineering fields and are available in commercial software packages which makes their use relatively easy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42]; DPY, Drucker-Prager yield; DLY, Drucker-Lode yield; PSD, principle strain damage [29]; LFD, Lee-Fenves plastic damage [22]; 1DY, one-dimensional yield; BM, Burger model; VMY, von Mises yield; VM+C+D, von Mises yield+cap+ element deletion; CIY, cast iron yield; BD, Brittle damage [17]; DPY(Q)+D, DPY(Q)+densification [19]; CZM, cohesive zone model; PFM, phase-field model; DPD+D, DP+Q damage onset+element deletion; GMM, generalized Maxwell model found: first, direct homogenization of the apparent level by using bone density (power laws [16,45]) and, in some cases, the orientation of the trabecular network (fabric [31,32] Damage and Fracture Interestingly, models including fracture mechanics became increasingly popular in the last years. Either rather simple "element deletion" models [46,51] or more sophisticated fracture energy-based models [26,45] have been published. Such approaches are more and more used in engineering fields and are available in commercial software packages which makes their use relatively easy.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, models including fracture mechanics became increasingly popular in the last years. Either rather simple “element deletion” models [ 46 , 51 ] or more sophisticated fracture energy-based models [ 26 , 45 ] have been published. Such approaches are more and more used in engineering fields and are available in commercial software packages which makes their use relatively easy.…”
Section: Review Of Recent Constitutive Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructural failure and reduction in whole‐bone mechanical properties are critical indicators of age‐related osteoporotic hip fracture. Ex vivo high‐resolution microCT‐based FEA has shown that initial failure of the proximal femur under sideways fall loading is associated with failure of just a tiny proportion of the bone tissue 29,30 . MRI‐FEA is able to assess microstructural and whole‐bone mechanical behavior of the hip without exposing subjects to ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…(12) and (14). First, using the spin tensor 14was used in [120][121][122][123][124][125][126][127] for modeling of the biological tissues, however, without referencing sources [117][118][119]. Third, the present model reflects the characteristic features of the anisotropic bimodular materials [128,129].…”
Section: Fig 12 Stiffening Of Meningioma As Measured By Mre : Ct Immentioning
confidence: 99%